Antibacterial activity of miloxacin. - Izawa, A (1980)
The chemotherapeutic properties of miloxacin (5,8-dihydro-5-methoxy-8-oxo-2H-1,3-dioxolo-[4,5-g]quinoline-7-carboxylic acid) have been compared with those of oxolinic acid and nalidixic acid. The in vitro activities of miloxacin (minimum inhibitory concentrations) against a variety of gram-negative bacteria, especially Enterobacteriaceae and Haemophilus, were comparable to those of oxolinic acid and 8 to 16 times greater than those of nalidixic acid. Miloxacin was more active than oxolinic acid against some anaerobes and less active against staphylococci. Miloxacin exhibited significant activities when administered orally to mice infected with Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Proteus vulgaris, or Serratia marcescens. Its efficacy was comparable to that of oxolinic acid and two to four times greater than that of nalidixic acid. Miloxacin was less active against a Pseudomonas aeruginosa infection and inactive at the maximum test doses against a Streptococcus pyogenes infection.